Treating Equals Unequally - Incentives in Teams, Workers' Motivation and Production Technology - Sebastian J. Goerg; Sebastian Kube; Ro'i Zultan (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
The importance of fair and equal treatment of workers is at the heart of the debate in organizational management. In this regard, we study how reward mechanisms and production technologies affect effort provision in teams. Our experimental results demonstrate that unequal rewards can potentially increase productivity by facilitating coordination, and that the effect strongly interacts with the exact shape of the production function. Taken together, our data highlight the relevance of the production function for organization construction and suggest that equal treatment of equals is neither a necessary nor a sufficient prerequisite for eliciting high performance in teams.
Keywords: C92; D23; D63; J31; J33; J41; M12; M52; 330; team incentives; equity; production function; social preferences; laboratory experiment; discriminating mechanism; mechanism design; Gruppenarbeit; Leistungsanreiz; Leistungsprinzip; Gerechtigkeit; Produktionsfunktion; Mechanism Design; Test